Answer:
Option B
center (3,2)
radius 3
Explanation:
Given:
x^2+y^2-6x+4y+4=0
x^2+y^2-6x+4y=-4
Now completing square of x^2-6x by introducing +9 on both sides:
x^2-6x+9+y^2+4y=-4+9
(x-3)^2+y^2+4y=5
Now completing square of y^2+4y by introducing +4 on both sides:
(x-3)^2+y^2+4y+4=5+4
(x-3)^2 + (y-2)^2= 9
Now comparing with the circle equation:
(x-h)^2 + (y-k)^2= r^2
where
r= radius of circle
h= x-offset from origin
k= y-offset from origin
In given case
r=3
h=3
k=2
Hence, option B is correct with radius =3 and center =(3,2)!